Weight Loss Associated With Employee Income in an Incentivized Employee Wellness Program. Issue 12 (December 2016) - Fink, Jennifer T.; Rich, Jennifer; Smith, David R.; Singh, Maharaj; Sutton, Kelly; Mueller, George; Ihrke, Doug M.; Skalla, Jessica L.; Cisler, Ron A.
Abstract : Objective: We examined the relationship between the type of incentivized wellness program and employee weight loss and the effects of participant income. Methods: We retrospectively examined employees who participated in one of six weight loss wellness programs, which were categorized for the present analysis: reweigh/body mass index, Coaching, and Weight Watchers/Meal Replacement. Those who participated were eligible for a 350/year insurance premium discount. Results: Employees in the low-income category of 45K or less participated at a higher rate, however, did not lose as much weight as those participants in the higher income categories of 70K or more. We found a positive association with weight loss in two of the categories, reweigh/body mass index, and Weight Watchers/Meal Replacement programs. Conclusion: Wellness programs have a significant impact on employee weight loss, but this relationship may vary across the income level of participants.